2022
DOI: 10.1186/s13568-022-01439-1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of epiphytic bacterial communities on male and female Sargassum thunbergii

Abstract: The epiphytic bacteria are the most abundant microorganisms on marine macroalga. However, there are few studies on the distribution of these epiphytic bacteria on male and female Sargassum thunbergii. In this study, the composition and diversity of epiphytic bacterial communities on male and female S. thunbergii were investigated by using the traditional culture-based method and 16S rDNA high-throughput sequencing. The results showed that the dominant bacterial phyla and genera were the same on both male and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…According to Hurd et al (2014), another mechanism of metal tolerance in marine macroalgae involves the ability of microorganisms that inhabit the algal surface to sequester metals by adsorption or detoxification. Several complex mechanisms are involved in macroalgae-bacteria interactions (Martin et al, 2014;Kouzuma and Watanabe, 2015;Ramanan et al, 2016;You et al, 2021;Wang et al, 2022). These interactions have received little attention in relation to metal pollution (see Paix et al, 2021;You et al, 2021).…”
Section: Sequestration By Microfoulingmentioning
confidence: 99%
“…According to Hurd et al (2014), another mechanism of metal tolerance in marine macroalgae involves the ability of microorganisms that inhabit the algal surface to sequester metals by adsorption or detoxification. Several complex mechanisms are involved in macroalgae-bacteria interactions (Martin et al, 2014;Kouzuma and Watanabe, 2015;Ramanan et al, 2016;You et al, 2021;Wang et al, 2022). These interactions have received little attention in relation to metal pollution (see Paix et al, 2021;You et al, 2021).…”
Section: Sequestration By Microfoulingmentioning
confidence: 99%
“…In fact, sex can lead to differences in the morphology, structure and function of dioecious plants (Tang, 2020;Lu et al, 2021;Zeng et al, 2022), and there are also some differences in enzyme activity (Chen et al, 2020), secondary metabolites (Li et al, 2022) and endogenous hormone levels (Ge et al, 2021), but there have been few studies on sex differences in endophytic bacteria in plants. Some studies have revealed differences in epiphytic bacterial communities in plants of different sexes, such as in Populus cathayana (Liu et al, 2021), Sargassum thunbergii (Wang et al, 2022b), and Porphyra haitanensis (Yang et al, 2022). However, for marine macroalgae, whether sex has an impact on the assembly of endophytic bacterial communities is still unknown.…”
Section: Introductionmentioning
confidence: 99%